The Effect of Leadership Competences on Job Satisfaction in Government Organization in Minahasa Region - Devyano V.F. Ranti (Journal of International Conference Proceedings (JICP), 2018)
This study aims to analyze the relationship of leadership competence and its impact to build job satisfaction in the organization with a quantitative approach. The research was conducted in government organizations in Minahasa Region, using Survey or correlational method. Sampling technique is nonprobability sampling type. Data collection techniques are observation, questionnaire, interview and documentation. Based on the discussion of the results of research analysis found leadership competencies such as personal, social, decision making, and fuctional competencies have significant positive affect on employee job satisfaction. Which means between the better leadership competence is also will affect stronger employee job satisfaction. Keywords: Leadership Competence, Employee Job Satisfaction